Histopathological Study of Gastric Lesions and its Correlation with Mucin Histochemistry and Helicobacter Pylori Infection - Deka, Alankrita; Sharma, Adity; Bhuyan, Ratna K; Paul, Sanjay LN (Annals of Pathology and Laboratory Medicine, 2021)
Background: Gastric disorders are responsible for a great deal of mortality and morbidity and are one of the most common encountered problems in clinical practice. H. Pylori infection is responsible for majority of acid peptic disease and is also a known carcinogen. Intestinal metaplasia is considered a precancerous lesion. We studied the incidence of H. pylori infection and mucin histochemistry of different gastric lesions. Methods: This study was conducted for a period of 1 year, in 50 gastric specimens received for histopathological study in the Department of Pathology, AMCH. Slides were stained with routine H&E and Giemsa for H. pylori detection. PAS/AB stain (at pH 2.5 & pH 1.0) was done to study mucin histochemistry. Results: Out of 50 cases, 58% cases were malignant and 42% cases were benign. H. Pylori was seen in 42% cases. IM was observed in 40% of gastric lesions. IM was more common in malignant lesions. On subclassification, Type 1 and 2 IM were seen almost equally in both benign and malignant gastric lesions, but Type 3 IM was more common in malignant lesion. Incidence of IM was higher in intestinal than diffuse adenocarcinoma. A statistically significant association was seen between H. Pylori infection and IM. Conclusion: Routine detection of H. pylori by special stains and mucin study in all gastric biopsy specimens helps in early detection of precancerous gastric lesions.